Chocolate Fountain Dreams Enterprise / Mohammad Farid Ag Omar ... [et al.] - Ag Omar, Mohammad Farid; Mohd Kamil, Siti Hawa; Madi, Farah Nadia; Sabdali, Fatimah Fahrozni; Tumin, Mohd Fakhrurazy (2009)
Nowadays, for those of any entrepreneur that involve themselves in the chocolate market can get better profit from these ideas which is halal and healthy chocolate. Halal is roper or legitimate; the fund earns halal profits in full compliance with the Shari'a. This is because; in our country especially in Sabah, there is only having several amount of entrepreneur that involves in the chocolate market. Our country has to import the chocolate from the other country to fulfill the demand in the country. In Sabah, the quantity of producing chocolate is less than other state. Supplier need to import chocolate from other state to fulfill the demand in Sabah. Therefore, from all of this reason our group has made decision to choose chocolate product as our entrepreneurship project. Our group chooses these chocolate because it brings many benefits such as;